Nanometer-optical-coating-based visibly tinted films with 24-hour sub-atmospheric passive cooling - Lee, Eun-Joo; Cho, Jin-Woo; Kim, Young-Seok; Kim, Sun-Kyung (Optics letters, 2021)
Colored films absorb solar radiation at specific visible wavelengths, and they consequently heat up above atmospheric temperatures when exposed to sunlight. In this Letter, we report nanometer-thick TiN-based multilayers of light cyan, magenta, and yellow colors that can provide 24 h sub-atmospheric cooling when covered with high-emissivity polymers. Outdoor experiments have demonstrated that these visibly tinted films retain sub-atmospheric temperatures during daytime and nighttime. All fabricated films generated almost color-independent cooling powers and even surpassed commercial white paint at TiN thicknesses <5nm. Our work thus highlights the potential of multispectral selective absorbers as esthetic passive coolers.Colored films absorb solar radiation at specific visible wavelengths, and they consequently heat up above atmospheric temperatures when exposed to sunlight. In this Letter, we report nanometer-thick TiN-based multilayers of light cyan, magenta, and yellow colors that can provide 24 h sub-atmospheric cooling when covered with high-emissivity polymers. Outdoor experiments have demonstrated that these visibly tinted films retain sub-atmospheric temperatures during daytime and nighttime. All fabricated films generated almost color-independent cooling powers and even surpassed commercial white paint at TiN thicknesses <5nm. Our work thus highlights the potential of multispectral selective absorbers as esthetic passive coolers.